1991
DOI: 10.1007/bf00028407
|View full text |Cite
|
Sign up to set email alerts
|

Salinity tolerance and morphology of the osmoregulation organs in Cladocera with special reference to Cladocera from the Aral sea

Abstract: The hyperosmotic regulation of adult Cladocera is determined mainly by the amount of salts consumed with the food and by reabsorption of salts in cells of the nuchal (neck) organ . The hypoosmotic regulation both in adults and embryos is determined mainly by excretion of salts in special epipodite cells or in cells of the nuchal (neck) organ . The salinity of the Aral sea for the last 30 years increased from 8-10% to 26-28%, which led to changes in the Cladocera fauna. At present only 4 species of Cladocera in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 7 publications
0
38
0
Order By: Relevance
“…Little information is available, either on the salinity tolerance and osmoregulatory organs in microcrustaceans (Aladin 1991), or on the biological response and adaptations in the freshwater species that invade brackish waters (Arne'r and Koivisto 1993). Freshwater cladocerans are hypertonic to their medium and the fluxes of water and solutes to or from the surrounding water could be considerable, but they have reduced their osmotic load by means of impermeable bodies and a low internal concentration of solutes in the epithelial cytoplasm, from which they are sodium pumped to the hemolymph-the major mechanism for osmoregulation in freshwater cladocerans (Peters 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little information is available, either on the salinity tolerance and osmoregulatory organs in microcrustaceans (Aladin 1991), or on the biological response and adaptations in the freshwater species that invade brackish waters (Arne'r and Koivisto 1993). Freshwater cladocerans are hypertonic to their medium and the fluxes of water and solutes to or from the surrounding water could be considerable, but they have reduced their osmotic load by means of impermeable bodies and a low internal concentration of solutes in the epithelial cytoplasm, from which they are sodium pumped to the hemolymph-the major mechanism for osmoregulation in freshwater cladocerans (Peters 1987).…”
Section: Discussionmentioning
confidence: 99%
“…When salinity causes the medium to become chronically hypertonic with respect to the cladocerans, the available mechanisms for osmoregulation are rather limited, as these species have not developed any evolutionary adaptation to the new conditions. Nevertheless, they are capable of short-term physiological adaptations to minimize the effects of salinization (Aladin 1991).…”
Section: Discussionmentioning
confidence: 99%
“…As the genus Daphnia is freshwater in origin and distribution, I did not expect to find reduction in fresh- water adaptation . Since D. magna osmoregulates up to a salinity of about 5%o in the external medium and above this salinity it is an osmoconformer (Fritsche, 1916 ;Aladin, 1991), it seems likely that a reduction in the ability to osmoregulate is involved in the loss of freshwater adaptation . It is sometimes suggested that a trade-off might exist between fitness under favourable conditions and stress resistance (review in Hoffmann & Parsons, 1991) .…”
Section: Comparability Of Data Setsmentioning
confidence: 99%
“…Many Cladocera, particularly daphnids, do not survive at salinity values above 3-4 per mille (e.g. see Dwyer et al, 1992;Jeppesen et al, 1994) which is what is presently experienced in Hickling Broad in summer, other Cladocera may be more tolerant and there are some which survive at quite high salinities (see Alonso, 1990Alonso, , 1991Aladin, 1991). There also appears to be a great deal of genetically based ecotypic variation within zooplankton species with differential adaptation to local conditions (Weider & Hebert, 1987;Mort, 1991).…”
Section: Very Highmentioning
confidence: 99%